Understanding and Promoting Birth Satisfaction in New Mothers. Issue 4 (July 2017) - Hinic, Katherine
Abstract: Purpose: The purpose of this study was to examine the impact of select maternal psychosocial and experiential factors on birth satisfaction of new mothers during early postpartum. Study Design and Methods: This is a descriptive correlational study exploring the relationships among birth satisfaction, breastfeeding self-efficacy, and perceived stress in 107 new mothers in the first 4 days postpartum. Instruments used included the Birth Satisfaction Scale-Revised, the Perceived Stress Scale, the Breastfeeding Self-Efficacy Scale-Short Form, and a researcher-generated demographic form. Quantitative analysis included descriptive statistics, correlation, one-way Analysis of Variance, and multiple linear regression. Results: Birth satisfaction was negatively correlated with perceived stress ( r = -.299, p < .05) and positively correlated with feeling prepared for birth ( rho = .243, p < .05) and breastfeeding self-efficacy ( r = .226, p < .05). The predictive model for birth satisfaction was significant ( R 2 = .204, F [6, 99] = 4.225, p = .001), explaining approximately 20.4% of variance in birth satisfaction in the sample. Clinical Implications: Stress reduction and management, establishment of realistic expectations for labor and birth, and promotion of togetherness with newborn immediately after birth are nursing priorities to promote birth satisfaction. Abstract : How do new mothers perceive the birth process? What contributes to their satisfaction with their childbirth experince? This study examines these issues among a group of new mothers during the first few days postpartum and offers insights on the type of care that women appreciate and desire during labor and birth.